Building financial literacy during the COVID-19 pandemic - Guna Ciemleja; Konstantins Kozlovskis (Entrepreneurship and Sustainability Issues, 2021)
The main objective of the present research is to identify importance of financial literacy is growing in such economically and socially difficult situations. The aim of the study was to find out how a COVID-19 pandemic affects people's decisions regarding personal financial management in Latvia. The research is based on the analysis of the theoretical literature and quantitative analysis based on structured questionnaire was used to obtain empirical data. Empirical data processing and analysis were carried out in SPSS statistical package. The article findings trends, in Latvian households before COVID-19 over the last decade, the risk of poverty has increased convincingly certain groups in society. Affected by pandemic people's shopping habits have changed. Pandemic time led to changes in consumer attitudes and behavior, society's lifestyles and on the financial position of households. Under the restrictions imposed on preventing epidemic spread, household consumption decreased and create unplanned savings. Savings ensure the financial stability of households during the economic downturn.